Make your organization a center of innovation : tools and concepts to solve problems and generate ideas - Hijfte, Stijn van (Apress, 2021)
The call for innovation within both society and all sectors of enterprise at large grows louder every day. In order to achieve this, organizations need to attract talent with the insight and creativity necessary to be able to understand the needs of not only this generation, but also future generations. Make Your Organization a Center of Innovation introduces key frameworks that can be adapted to any business or team focused on innovation. Some aspects that are crucial for an organization to become a center of innovation are change management, process mining, and overall company strategy. Author Stijn Van Hijfte also introduces you to newer techniques that are still making their way up the ladder to overall industry adoption. These include AI, blockchain, and intelligent automation. Van Hijfte also takes care to ensure you choose the right innovation strategy for your specific company goals, as opposed to solely showing off the latest industry trends within the topic. Make Your Organization a Center of Innovation is perfect for business leaders, students, recruiters, and more. You will come away with insights about how to best prepare your teams stakeholders for the changes that innovation brings. The mission and vision of your organization should always be promoting new ideas, but a roadmap is needed to implement them effectively. Make Your Organization a Center of Innovation is the guide youve been seeking.